2007
DOI: 10.1111/j.1551-2916.2007.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy and Nuclear Magnetic Resonance Studies of Geopolymers for Radioactive Waste Immobilization

Abstract: Transmission electron microscopy of a geopolymer phase, derived from metakaolin and alkaline silicate solutions and having nominal Na/Al and Si/Al molar ratios of 1 and 2, respectively, showed it to be amorphous on the ∼1 nm scale after curing at 40°C. In samples containing 5 wt% Cs or Sr, Cs inhabited the amorphous phase, whereas Sr was incorporated only partly, being preferentially partitioned to crystalline SrCO3. Heating progressively to dewater the material had little effect on the overall structure for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 33 publications
5
48
0
2
Order By: Relevance
“…observations of Blackford et al (2007). It is of interest that no crystalline zeolites are observed in any samples, even for these samples with relatively high water content after 100 days' moist curing; this correlates with the observations of Provis et al (2005) that zeolite formation is notable only at low soluble silicate content for samples cured at moderate temperatures.…”
Section: Degrees 2θsupporting
confidence: 75%
See 2 more Smart Citations
“…observations of Blackford et al (2007). It is of interest that no crystalline zeolites are observed in any samples, even for these samples with relatively high water content after 100 days' moist curing; this correlates with the observations of Provis et al (2005) that zeolite formation is notable only at low soluble silicate content for samples cured at moderate temperatures.…”
Section: Degrees 2θsupporting
confidence: 75%
“…Fig. 2b shows that the Sr-containing samples display somewhat more complex behaviour; in particular, insoluble SrCO 3 forms in all Sr-containing samples as previously noted for the nitrate case (Blackford et al, 2007). Even the sample where Sr was added as the relatively insoluble SrSO 4 (K sp = 2.…”
Section: Instrumental Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Immobilization of lead by geopolymers has attracted much study, and has been suggested to occur by the chemical formation of an insoluble lead silicate rather than by physical entrapment within the geopolymer pore structure (27 (28). Incorporation of radioactive Sr in the amorphous geopolymer matrix does not occur to any great extent, mostly by the formation of crystalline SrCO 3 rather than in a chargebalancing role (29). All these studies suggest that by analogy with flyash-based geopolymers, the present materials prepared by alkali treatment of milled pond ash might result in the retention of the hazardous elements inside the the geopolymer binder paste, as has been found to be the case.…”
Section: Leaching Of Heavy Metals From the Geopolymersmentioning
confidence: 99%
“…The soil mineral dissolution followed the order of quartz fi kaolinite fi illite, and although cancrinite, sodalite, and zeolite were formed, the zeolite was not detected after 25 days of reaction time (Mashal et al 2005a), indicating that this mineral underwent either dissolution or phase transformation. Other relevant references follow: Gerson and Zheng 1997;Hassan 1997;Zheng et al 1997;Barnes et al 1999a;Green-Pedersen and Korshin 1999;Park and Englezos 1999;Buhl et al 2000;Buck and McNamara 2004;Zhao et al 2004;Bao et al 2005;Blackford et al 2007;Chorover et al 2008;and Leyva-Ramos et al 2008. 3.1…”
Section: 7mentioning
confidence: 99%